Catch me if you can? Staggered inevitable disclosure doctrine ( IDD ) rejection and entrepreneurial activity in the US - Patel, Pankaj C.; Devaraj, Srikant (Strategic Entrepreneurship Journal, 2022)
Abstract Research Summary Inevitable disclosure doctrine (IDD) refers to a legal doctrine where an employer can claim, without the need for proof or evidence, misappropriation of trade secrets to seek an injunction against an employee. Based on entrepreneurial spawning literature, for employees seeking to start their ventures, IDD rejection by state courts could therefore be a potential catalyst to entrepreneurial activity. In a sample of neighbor‐counties across state borders with and without IDD rejection, the two‐way fixed‐effects difference‐in‐differences estimates show positive effects for county‐level entrepreneurial outcomes. However, when applying more recently developed methods for testing staggered implementation, we find no support for county‐level entrepreneurial outcomes across multiple specifications and heterogeneities. The findings have implications for the limited efficacy of IDD rejection on regional entrepreneurial activity. Managerial Summary The value of protecting trade secrets is important for employers, and the role of laws in preventing employees from potentially disclosing their trade secrets is widely studied. One such legal doctrine is the inevitable disclosure doctrine (IDD) where an employer can claim, without the need for proof or evidence, misappropriation of trade secrets to seek an injunction against an employee. We find that IDD rejections by courts have a limited effect on the formation of startups in a county. The findings imply that investors are less encumbered by IDD rejections by courts and that policymakers may not find IDD rejections as a useful mechanism to prime local entrepreneurship.